Mitigation of methane gas emission in rice by drip irrigation [version 1; peer review: 2 approved] - Theivasigamani Parthasarathi; Koothan Vanitha; Sendass Mohandass; Eli Vered (F1000Research, 2019)
Background: Rice farming faces major challenges, including water limitation, drought and climate change in the current scenario of agriculture. Among the innovative water-saving techniques, drip irrigation is a forerunner, with maximized water-saving potential, increased grain yield and methane mitigation. Methods: A field experiment was conducted comprising four different drip irrigation practices: (i) sub-surface drip irrigation (SDI) with 1.0 litre per hour (lph) discharge rate emitters (DRE) (SDI+1.0 lph DRE) (ii) SDI+0.6 lph DRE, (iii) surface drip irrigation (DI) with 1.0 lph discharge rate emitters (DI+1.0 lph DRE), (iv) DI+0.6 lph DRE and were compared with (v) a conventional flood aerobic irrigation (considered conventional). Results: The estimated grain yield of rice was found to be 23.5%, 20.3%, and 15.1% higher under SDI+1.0 lph DRE, SDI+0.6 lph DRE and DI+1.0 lph DRE practices, respectively, than the conventional method. A water saving of 23.3% was also observed for all drip practices compared with conventional practices. Seasonal methane emission flux declined 78.0% in the drip methods over the conventional irrigation: better mitigation than previously reported values (alternate wetting and drying (47.5%) and system of rice intensification (29.0%) practices). Continuous soil aeration and enhanced soil methanotrophs (P<0.05) limit the peak methane emission in rice during the flowering phase in drip irrigation, which is reflected in the methane emission flux values. Consequently, the equivalent CO2 (CO2-eq) emissions and yield-scaled CO2 eq-emission were found to be significantly lower in SDI (43.8% and 49.5%, respectively), and DI (25.1% and 26.7%, respectively) methods as compared with the conventional that ensures better methane mitigation and future climate-smart rice production systems. Conclusions: Drip irrigation could reduce the cumulative methane emission in aerobically grown rice. SDI + 1.0 lph DRE practice can be applied in areas with inadequate water availability and effective in reducing the CO2-eq emission with better yield than conventional.